Shrines surrounding the Mahanaleshwar Temple - Temples of India Project Team (2024)
View of the west-facing elevations of the two shrines facing the Mahanaleshwar Temple. These temples are built in red sandstone, consisting of plain plinth mouldings, geometric motifs on the wall subsidiary projections and deep niches in the principal projections. No icons on the temple walls. Shekhari variety of shikhara.